Culturally Informed Ethical Decision-Making in Situations of Suspected Child Abuse - Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2007)
As part of their role as helping professionals, counsellors are required to make a report to Child Welfare authorities when they have reason to believe that a child has been harmed or neglected. The introduction of unique cultural practices through the international migration of immigrants and refugees to Canada has blurred the boundary between acceptable and unacceptable parental behaviour. This paper informs counsellors about important factors to consider in determining whether to classify culturally sanctioned practices as helpful or harmful to children. It also outlines the types of information and documentation that would be required to justify the challenge of a practice viewed to be culturally acceptable among members of a specific group under Canadian legislation and ethical codes.